Peran Konseling Islam Dalam Membantu Mengelola Stres Akademik Siswa Di SMK IPTEK Weru Sukoharjo - AnggrainiPutri; Nur Utami, Rizky; Nur Alifazahro, Nadhifa; Brilliant Bilqis, Hilda; Oktavia, Devi (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
Adolescents who are still in school are vulnerable to feeling academic stress. This study aims to find out about academic stress and the role of Islamic counseling in managing it at SMK Iptek Weru Sukoharjo. This type of research is descriptive qualitative research. Data collection techniques using interviews, observation, and documentation. The data sources of this research are the results of interviews with counseling teachers and literature studies. The results of the research are Academic stress is a situation or condition in which there is a mismatch between environmental demands and the abilities possessed by students, so that students feel increasingly burdened by various pressures and demands. Examples of academic stress in SMK Iptek students are missing school, skipping class, being alone, always sleeping in class, and never doing assignments. Factors that trigger academic stress are competition between friends and even between classes, teachers who emphasize that all students must be able and assume that all students' abilities are the same as well as the absence of complete facilities and provided by the school. Therefore, the role of Islamic counseling is present in helping to manage academic stress by collaborating with PAI teachers in providing motivation, material in stress management and so on as well as material about character.